2010
DOI: 10.1016/j.jcmg.2010.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular and Extravascular Microvessel Formation in Chronic Total Occlusions

Abstract: Differences are present in the temporal and geographic patterns of intravascular and extravascular microvessel formation during CTO maturation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 22 publications
1
29
1
1
Order By: Relevance
“…Yet once the CTO has matured, the number of both extra-and intravascular microchannels become much fewer, compared with the early phase (12). Upon further analysis, the longitudinal continuity of microchannels extended to approximately 85% of the entire CTO length, except in the early phase of CTO (12).…”
Section: Microchannelloosetissuesegmentsmentioning
confidence: 95%
See 1 more Smart Citation
“…Yet once the CTO has matured, the number of both extra-and intravascular microchannels become much fewer, compared with the early phase (12). Upon further analysis, the longitudinal continuity of microchannels extended to approximately 85% of the entire CTO length, except in the early phase of CTO (12).…”
Section: Microchannelloosetissuesegmentsmentioning
confidence: 95%
“…In an experimental rabbit femoral artery CTO model, microcomputed tomography demonstrated that extravascular microchannels are seen mostly in the early phase of artery occlusion, and in more mature CTO, intravascular microchannels increase gradually (12). Yet once the CTO has matured, the number of both extra-and intravascular microchannels become much fewer, compared with the early phase (12).…”
Section: Microchannelloosetissuesegmentsmentioning
confidence: 99%
“…Some noninvasive methods, such as radiological imaging techniques, have been employed to evaluate the morphologic features of vascularization in engineered tissues. 9 Micro-CT provides a good rendering of the 3D structure of the vessels, 10 and magnetic resonance imaging can be used to track groups of cells as a stream when cells are labeled with a contrast agent or reporter probe. 11 However, each of the current radiologic imaging techniques lack the cellular-level resolution required to distinguish one cell from another.…”
Section: Introductionmentioning
confidence: 99%
“…The cellular and molecular processes control vascular healing after stent implantation in non-CTO lesion [23]. It has been reported that CTO lesions develop from a total luminal obstruction of coronary arteries by a thrombus, subsequently are organized by inflammatory cells followed by infiltrating smooth muscle cells, and generate proteoglycan matrix as well as calcification [24,25]. Thus, true-lumen in CTO lesion is pathologically different from true-lumen in non-CTO lesion.…”
Section: Discussionmentioning
confidence: 99%